Modified thermal periodic Poiseuille and Lees-Edwards boundary conditions for energy conservative dissipative particle dynamics - Zhao, Jiayi; Chen, Shuo; Zhu, Liming; Liu, Yang (International communications in heat and mass transfer, 2021)
Two kinds of thermal boundary conditions without wall particles in energy conservative dissipative particle dynamics method are investigated in present paper. Firstly, the original thermal periodic Poiseuille flow (PPF) was improved to avoid the unreasonable temperature shift by rebuilding the thermal equilibrium. Then a novel thermal Lees-Edwards (LE) boundary condition was proposed. The constant temperature gradient and uniform density distribution are obtained by rescaling the interaction between particle pairs, and the velocity components of particles for particles re-entering the boundaries. Finally, both the temperature and velocity gradient are integrated into the thermal LE to simulate a constant temperature different in a shear flow. The thermal LE provides a new way to study the thermal-mechanical coupled problems with less computational cost and artificial fluctuation of properties compared with traditional wall particle boundary conditions. Furthermore, it can also be easily extended to related particle-based methods, such as molecular dynamics and Brownian dynamics, etc.